2009
DOI: 10.1186/1471-2164-10-408
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic transcription gene profiles under the modulation of nitric oxide in nuclear run on-microarray and proteomics

Abstract: Background: Microarray analysis still is a powerful tool to identify new components of the transcriptosome. It helps to increase the knowledge of targets triggered by stress conditions such as hypoxia and nitric oxide. However, analysis of transcriptional regulatory events remain elusive due to the contribution of altered mRNA stability to gene expression patterns as well as changes in the half-life of mRNAs, which influence mRNA expression levels and their turn over rates. To circumvent these problems, we hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 51 publications
0
22
0
Order By: Relevance
“…SCD1 is one of the target genes upregulated under hypoxic stress . In our study, using the human VHL‐deficient RCC line 786‐0, which has constitutively expressed HLF‐2α and gives a model to investigate the effects of HLF‐2α on its target genes, we found that SCD1 is upregulated under hypoxia and modulated by HLF‐2α.…”
Section: Discussionmentioning
confidence: 65%
“…SCD1 is one of the target genes upregulated under hypoxic stress . In our study, using the human VHL‐deficient RCC line 786‐0, which has constitutively expressed HLF‐2α and gives a model to investigate the effects of HLF‐2α on its target genes, we found that SCD1 is upregulated under hypoxia and modulated by HLF‐2α.…”
Section: Discussionmentioning
confidence: 65%
“…To corroborate this point, a recent study using a combined approach of nuclear run on and microarray analysis compared the genetic profile of RAW 264.7 macrophages treated with hypoxia and/or DETA/NONOate [109]. This study identified 162 transcripts that were regulated only when cells were co-treated with hypoxia and NO as well as detecting 14 genes that were under the influence of both hypoxia and NO alone and were differentially regulated by the two treatments in combination.…”
Section: Involvement Of Hif In Inflammatory Diseasesmentioning
confidence: 92%
“…Atf3, a stress gene activated by ischemia/hypoxia (41,42), was increased ϳ2.5-fold in cRyr2KO hearts (Fig. 6G).…”
Section: Ryr2 Deletion Reduces Camentioning
confidence: 96%